2022
DOI: 10.1038/s41598-022-19093-9
|View full text |Cite
|
Sign up to set email alerts
|

Stability and volatility shape the gut bacteriome and Kazachstania slooffiae dynamics in preweaning, nursery and adult pigs

Abstract: The gut microbiome plays important roles in the maintenance of health and pathogenesis of diseases in the growing host. In order to fully comprehend the interplay of the gut microbiome and host, a foundational understanding of longitudinal microbiome, including bacteria and fungi, development is necessary. In this study, we evaluated enteric microbiome and host dynamics throughout the lifetime of commercial swine. We collected a total of 234 fecal samples from ten pigs across 31 time points in three developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…Thus, K. slooffiae might exhibit powerful metabolic activities in the intestinal tract and plays a critical regulatory role in host metabolism. Previous studies have also identified K. slooffiae as a member of the intestinal yeasts in pigs [ 7 , 30 , 38 , 86 , 112 117 ] and have shown that K. slooffiae can produce some bioactive substances, such as peptides, formic acid, and dehydroascorbic acid [ 118 ]. The total nitrogen and amino acid contents of K. slooffiae were higher than those of S. cerevisiae [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, K. slooffiae might exhibit powerful metabolic activities in the intestinal tract and plays a critical regulatory role in host metabolism. Previous studies have also identified K. slooffiae as a member of the intestinal yeasts in pigs [ 7 , 30 , 38 , 86 , 112 117 ] and have shown that K. slooffiae can produce some bioactive substances, such as peptides, formic acid, and dehydroascorbic acid [ 118 ]. The total nitrogen and amino acid contents of K. slooffiae were higher than those of S. cerevisiae [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported increasing Shannon alpha diversity values with less variability over time in the fecal bacteriome of piglets through the weaning transition ( 15 , 16 ). The current study found that alpha diversity of the fecal bacteriome increased between day 14 to day 21 and remained constant between day 21 and day 49.…”
Section: Discussionmentioning
confidence: 95%
“…This taxon is the dominant species of Kazachstania in the piglet around the weaning transition ( 16 ). K. slooffiae has been detected as early as 3 days after birth ( 46 ), and abundance peaks shortly after weaning ( 14 ), but decreases as the piglet matures past the growing phase into adulthood ( 15 ). Previously, we collected samples at day 35 (weaned at day 21), and K. slooffiae was indeed a dominant fungal community in the mycobiome at this time ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations